O efeito da carga oclusal no processo de reparo do ligamento periodontal após reimplante imediato em molar de ratos: avaliação histológica e imunoistoquímica - Beneti, Igor Mariotto [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
An ideal protocol treatment for cases of immediate or delayed tooth replantation hasn’t been developed yet, although tooth replantation is considered the best treatment in cases of tooth avulsion. Factors like extra-alveolar time, storage, contamination, dental rizogenesis phase, use of a splint, and occlusal trauma can interfere in the replantation prognosis. The normal occlusal function is a mechanical stimulus that is necessary for the maintenance of the homeostasis of periodontal tissue, whereas the absence or excess of occlusal load results in a disharmonic functioning of periodontal tissues. The aim of this study is to assess the influence of occlusal load during the repair process of immediate and delayed replantation of rat molars. They used 280 Wistar rats divided into three groups (normal occlusion, and infraocclusion supraoclusão) and a control group total, they were divided into nine periods. Qualitative and quantitative analysis will be performed in histological cuts, using the hematoxylin eosin staining protocol, and cells that display immunoreactivity to cellular apoptosis. The data will be submitted to variance analysis A or Kruskal-Wallis), using SPSS 16.0 at a significance level of p<0.05. In the initial period the thickness of the cervical third of the PDL of replanted teeth showed a statistically significant increase in all test groups, compared to the control group. A percentage reduction of blood vessel area, cell profile and PDL thickness was observed in the majority of studied periods. The supra-occlusal group showed a higher level of radicular resorption, followed by the normal and infra-occlusion groups. In face of the limitations of this study, it was concluded that the occlusal load absorbed by replanted teeth modifies the repair process of the PDL. Occlusal trauma accelerates the radicular resorption of replanted teeth significantly.

Busca-se ainda encontrar o melhor tratamento para os casos de reimplantes imediatos ou tardios, visto que estes seriam considerados os tratamentos ideais em caso de avulsão. Fatores como período extra-alveolar, meios de conservação, contaminação, fase de rizogênese dental, uso de contenção e trauma oclusal podem interferir no prognóstico dos reimplantes. A função oclusal favorável é um estímulo mecânico necessário para a manutenção da homeostasia dos tecidos periodontais, já a falta ou o excesso de carga oclusal resulta na desarmonia do funcionamento dos tecidos periodontais. O objetivo deste estudo foi avaliar o efeito da carga oclusal após o processo de reparo de reimplante imediato em molares de ratos. Foram utilizados 280 ratos wistars divididos em três grupos experimentais(oclusão normal, infraoclusão e supraoclusão) e um grupo controle total, os mesmos foram divididos em nove períodos. As análises qualitativas e quantitativas foram realizadas em cortes histológicos corados pelo método da hematoxilina e eosina, e imunorreatividade para apoptose celular. Os dados foram comparados através da análise de variância (ANOVA), Kruskal-Wallis e Bonferroni como teste post-hoc, considerando p<0,05 como significante. No período inicial (1 a 3 ou 5 dias) a espessura do espaço do LPD (ligamento periodontal) do terço cervical dos dentes reimplantados, apresentou um aumento estatisticamente significante da espessura em todos os grupos experimentais quando comparados ao grupo controle total. O grupo oclusão normal e infraoclusão apresentaram uma redução na porcentagem da área de vasos, perfil celular e espessura do espaço do LPD, na maioria dos períodos estudados. O grupo supraoclusão apresentou uma maior ...
Keywords: Reimplante dentário; Oclusão dentária traumática; Imuno-histoquímica; Tooth replantation